2016
DOI: 10.1155/2016/2156273
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Macular Edema Pathophysiology: Vasogenic versus Inflammatory

Abstract: Diabetic macular edema (DME) can cause blindness in diabetic patients suffering from diabetic retinopathy (DR). DM parameters controls (glycemia, arterial tension, and lipids) are the gold standard for preventing DR and DME. Although the vascular endothelial growth factor (VEGF) is known to play a role in the development of DME, the pathological processes leading to the onset of this disease are highly complex and the exact sequence in which they occur is still not completely understood. Angiogenesis and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
268
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(284 citation statements)
references
References 80 publications
1
268
0
15
Order By: Relevance
“…The importance of this balance goes hand-in-hand with the importance of the chronicity of DME in the variability observed in patient response to anti-VEGF treatment, because it is generally believed that DME is primarily mediated by VEGF in its early phase, whereas the involvement of other cytokines and inflammatory mechanisms becomes more important in chronic disease. 2 Low-grade inflammation has been postulated to be responsible for the retinal damage that occurs in chronic DME. 2 It may be important to treat the inflammatory component of DME in patients who do not respond adequately to anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this balance goes hand-in-hand with the importance of the chronicity of DME in the variability observed in patient response to anti-VEGF treatment, because it is generally believed that DME is primarily mediated by VEGF in its early phase, whereas the involvement of other cytokines and inflammatory mechanisms becomes more important in chronic disease. 2 Low-grade inflammation has been postulated to be responsible for the retinal damage that occurs in chronic DME. 2 It may be important to treat the inflammatory component of DME in patients who do not respond adequately to anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2 Low-grade inflammation has been postulated to be responsible for the retinal damage that occurs in chronic DME. 2 It may be important to treat the inflammatory component of DME in patients who do not respond adequately to anti-VEGF treatment. Studies have demonstrated the effectiveness of corticosteroid treatment in long-standing and refractory DME.…”
Section: Discussionmentioning
confidence: 99%
“…Tokom dužeg trajanja bolesti hiperglikemija dovodi do oštećenja endotela malih krvnih sudova, što se ogleda u gubitku pericita i zadebljanju bazalne membrane, a za posledicu ima povećanu propustljivost kapilara za sastojke plazme i sužavanje lumena kapilara (5). Patološka propustljivost kapilarne mreže, koja se klinički manifestuje kao edem makule, dovodi do zadrža-vanja tečnosti i lipoproteina u tkivu, što remeti arhitektoniku makule i ima za posledicu smanjenje oštrine vida (6). Edem retine lokalizovan van makule neprimetan je za pacijente jer ne smanjuje oštrinu vida (7).…”
Section: Uvodunclassified
“…Alasil i saradnici (23) navode da ne postoji korelacija između CMD i oštrine vida, ali da CMD predstavlja prognostički faktor. U našoj studiji ne postoji statistički značajna povezanost između poboljšanja oštrine vida i smanjenja centralne makularne debljine, što je u skladu sa nalazima Alasila i saradnika (23) i Romera i saradnika (6).…”
Section: Diskusijaunclassified
“…14 The mechanisms of action of these agents include nonspecific anti-inflammatory properties 14 ; VEGF is the primary mediator of the breakdown in blood-retinal barrier characteristic of DME. 2,15,16 The intravitreal anti-VEGF therapies, ranibizumab (Lucentis; Genentech, Inc., San Francisco, CA, USA) and aflibercept (Eylea; Regeneron, Inc., Tarrytown, NY, USA), have become the standard of care for DME, with functional and anatomical benefits evident in terms of improved visual acuity and associated decreases in retinal thickness. [17][18][19][20] Nevertheless, intravitreal therapy has limitations, and patients risk pain, short-and long-term increases in intraocular pressure (IOP), subconjunctival/vitreal hemorrhages, vitreous floaters, retinal detachment, and endophthalmitis.…”
mentioning
confidence: 99%